Remnants of Residency - Ahilan, P. (Institute of architects, 2024)
Archaeologists in western Cyprus discovered a group of wells that are believed to be the oldest in the world and proved it was 10,000 years old using radiocarbon dating. The oldest wells found at South Indian and Sri Lankan archaeological sites are estimat- ed to be more than 2,000 years old. Archaeologically, wells are earthen constructions created by driving, drilling or excavating to access waterways found amidst permeable rock layers underground. Terracotta, stone or brick were used to line the build- ing; wood was occasionally used to line wells dating back to the early Neolithic period. Wells differ historically in their design. They range from a straightforward scoop in a dry stream's silt to Iran's qanats, India's step wells and sakiehs and Jaffna's sutra kinaru, to square and round wells in many parts of the world. Tamil culture has a rich history of wells that vary widely in terms of location and architectural patterns.